Renewing innovation systems in agriculture and food How to go towards more sustainability? - Coudel, E. (Emilie) (Wageningen : Wageningen Academic Publishers, 2013)
Present-day society asks more from agriculture than just the production of food. Agriculture is now required to be concerned with the quality of food, ecosystem services, inclusion of marginalized populations, revitalization of rural territories, energy production, etc. This opening up of the future of agriculture encourages rural actors to experiment with new farming systems, using imagination, creativity and determination to replace dominant models. At the same time, low-cost mass-production systems continue on their way, with promises of a future based on green technologies. In this discussion it is important to consider what kind of sustainable development societies really want. Which innovations will help in achieving these developments? What role can research and public policies play in supporting the emergence of these innovations? This book takes the debate beyond the purely technical options and considers social and institutional innovations as well. It demonstrates that innovation is the result of a confrontation between visions of actors who often have divergent interests. There is no single path towards sustainable development and we must find ways to encourage the emergence and co-existence of different types of agriculture and food systems. The success of transitions will not only depend on our capacity to rethink existing models, but especially on our willingness to embark on a creative learning process from which we will inevitably emerge transformed.
Reconsidering innovation to address sustainable development / Guy Faure ... [et al.] -- Thinking innovation differently -- Standards governing agricultural innovation. Where do we come from? Where should we be going? / Lawrence Busch -- From concept to emerging practice: what does an innovation system perspective bring to agricultural and rural development? / Bernard Triomphe, Riikka Rajalahti -- Innovation systems of the future: what sort of entrepreneurs do we need? / Andy Hall, Kumuda Dorai -- Addressing new issues -- Innovating in cropping and farming systems / Jean-Marc Meynard -- Innovation and social inclusion: how to reduce the vulnerability of rurals? / Denis Requier-Desjardins -- Quality-driven market innovations: social and equity considerations / Estelle Bi{u296E}abe, Cerkia Bramley, Johann Kirsten -- Innovation and governance of rural territories / AndrTorre, Fric Wallet -- What implications for policy making and research? -- Agrobiodiversity: towards inovating legal systems / Juliana Santilli -- Policies to foster innovation in the Mediterranean region / Karim Hussein, Khalid El Harizi -- Designing innovative agriculture policies in Africa / Papa Abdoulaye Seck, Aliou Diagne, Ibrahima Bamba -- Conclusion: en route...but which way? / Bernard Hubert ... [et al.]
Includes bibliographical references.
Keywords: Agricultural innovations; Sustainable agriculture; Food industry and trade -- Technological innovations